Experiences and preferences for psychosocial support: a qualitative study exploring the views of patients with chronic haematological cancers - Rebecca Sheridan; Eve Roman; Alexandra Smith; Russell Patmore; Debra Howell; Dorothy McCaughan; Ann Hewison (BMJ Open)
Objectives Patients with chronic haematological cancers are often treated on a relapsing-remitting pathway, which may extend for many years. Such diagnoses are associated with uncertainties that often cause anxiety and distress, meaning patients (and families) are susceptible to potentially prolonged emotional difficulties, across the cancer journey. Experiences and preferences regarding psychosocial needs and support over time are relatively unexplored, which this study aimed to address.Setting and design Set within the UK’s Haematological Malignancy Research Network (an ongoing population-based cohort that generates evidence to underpin improved clinical practice) a qualitative, exploratory study was conducted, using semistructured interviews. Reflexive thematic analysis was used to assess the interview data via an exploratory, inductive approach, underpinned by the research questions.Participants Thirty-five patients were included with chronic lymphocytic leukaemia, follicular lymphoma, marginal zone lymphoma or myeloma; 10 of whom were interviewed alongside a relative.Results Five themes were identified from the data: (1) accessing support, (2) individual coping behaviour affecting support preferences, (3) divergent and fluctuating thoughts on patient support forums, (4) the role, influence and needs of family and friends and (5) other sources of support and outstanding needs. Findings suggest that patients’ individual attitudes towards support varied over time. This also influenced whether support was perceived to be available, and if it was then used.Conclusion This study highlighted the variation in preferences towards psychosocial support among patients with chronic haematological cancers. As patients can live for many years with significant emotional difficulties, they may benefit from frequent monitoring of their psychosocial well-being, as well as signposting to holistic support, if this is needed.